NILAI-NILAI PENDIDIKAN KARAKTER PADA TRADISI “MARDEMBAN” RITUAL MAKAN DAUN SIRIH PADA ETNIS BATAK TOBA DI DESA HUTA TINGGI - Sofi Mutiara Insani; Rosarina Giyartini; Anggit Merliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the process of implementing the mardemban tradition in the Toba Batak ethnicity, describe the function of the mardemban tradition, and describe the community's view of this tradition. This research uses a qualitative method with a descriptive approach. The research location is Huta Tinggi Village, Pangururan District, Samosir Regency. Data collection techniques were carried out through interviews with traditional leaders and local communities, as well as documentation of mardemban tradition activities. The results showed that the mardemban tradition is a ritual of eating betel leaves carried out in various traditional events, such as weddings and religious ceremonies. The function of the mardemban tradition is not only as a symbol of respect for ancestors, but also as a means of strengthening social relations and instilling cultural values to the younger generation. The community believes that the implementation of mardemban helps strengthen the cultural identity of the Toba Batak in the midst of increasingly modern times.